Menyibak Ketabuan: Sebuah Tinjauan Atas Social Marketing Program Pencegahan HIV-AIDS di Indonesia - Ameilia, Yera (Jurnal Aplikasi Manajemen, 2015)
HIV-AIDS cases has been increasing around the world and became one of theworrying problem faced by most parts of the world. Social marketing be one way that can bedone to reach social objectives in influencing people's behavior, including HIV-AIDS prevention.Social marketing programs can be applied for the prevention of HIV-AIDS, butsocial marketing of condoms be an effective way in preventing HIV-AIDS. Social marketingof condoms has been effectively implemented by various countries to raise public awarenessof used the condoms in preventing the transmission of HIV-AIDS, but the application of acondom social marketing program regarded taboo and supported with various problems inthe society. It makes Indonesian people lack awareness about condoms and do not understandthat the actual use of condoms is very important in the prevention of HIV-AIDS.